(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The main aim of this article is to study the problems of translating religious texts. The article highlights some serious problems of translating Islamic religious texts and suggests possible solutions for them by scholars of linguistics This article is mainly concerned with the difficulties and the challenges that translators are confronted with when they deal with religious texts.The main objective in this article is to draw the reader’s attention to the difficulties and challenges that I encountered while translating some religious extracts from books.